The need for annual echocardiography to detect cabergoline-associated valvulopathy in patients with prolactinoma: a systematic review and additional clinical data. Issue 11 (November 2015) - Caputo, Carmela; Prior, David; Inder, Warrick J
Summary: Present recommendations by the US Food and Drug Administration advise that patients with prolactinoma treated with cabergoline should have an annual echocardiogram to screen for valvular heart disease. Here, we present new clinical data and a systematic review of the scientific literature showing that the prevalence of cabergoline-associated valvulopathy is very low. We prospectively assessed 40 patients with prolactinoma taking cabergoline. Cardiovascular examination before echocardiography detected an audible systolic murmur in 10% of cases (all were functional murmurs), and no clinically significant valvular lesion was shown on echocardiogram in the 90% of patients without a murmur. Our systematic review identified 21 studies that assessed the presence of valvular abnormalities in patients with prolactinoma treated with cabergoline. Including our new clinical data, only two (0·11%) of 1811 patients were confirmed to have cabergoline-associated valvulopathy (three [0·17%] if possible cases were included). The probability of clinically significant valvular heart disease is low in the absence of a murmur. On the basis of these findings, we challenge the present recommendations to do routine echocardiography in all patients taking cabergoline for prolactinoma every 12 months. We propose that such patients should be screened by a clinical cardiovascular examination and that echocardiogram should be reserved for those patients with an audible murmur, those treated for more than 5 years at a dose of more than 3 mg per week, or those who maintain cabergoline treatment after the age of 50 years.